Islamic Wealth Management as a Framework for Micro and Small Enterprise Sustainability - Maksum Maksum; Aziz Muslim; Mukhamad Yazid Afandi (LAN TABUR: Jurnal Ekonomi Syariah The Islamic University of KH. Achmad Muzakki Syah Jember, East Java. Jember Jln. Manggar Gebang Poreng 139A Patrang Jember Jawa Timur, 2026)
Introduction: Micro and small enterprises (MSEs) in Muslim-majority countries face sustainability challenges amid economic instability and post-pandemic pressures. Conventional frameworks emphasize profit maximization but often overlook ethical and spiritual dimensions integral to Islamic values. This study develops Islamic Wealth Management (IWM) as a comprehensive framework for MSE sustainability through authentic Islamic principles. Methods: This exploratory study employs qualitative library research, analyzing classical Islamic texts, contemporary Islamic financial practices, and academic literature using content analysis techniques. Results: Five core IWM aspects (wealth creation, accumulation, protection, purification, distribution) form an integrated system supporting MSE sustainability across economic, social, and spiritual dimensions. This creates a sharia-based circular economy where wealth distribution becomes wealth creation, embodying Qur'anic principles of equitable circulation. Conclusion and suggestion: IWM provides a viable alternative to conventional sustainability models. Future research should develop measurement instruments for spiritual sustainability and examine institutional ecosystems required for effective implementation.